Evocação e janela de reconsolidação da memória: aplicações para o ensino de neurofisiologia - Elisa Michelstaedter Brochado (2023)
Memory retrieval induces a temporal window of molecular instability. It is believed that during this malleable time a preexisting memory trace can be updated through a process termed reconsolidation. Beyond this notion, in educational environment, students are constantly introduced to new concepts and often need to integrate them to understand complex systems. In this study, we tested the hypothesis that active learning methods induce the reactivation of previous consolidated knowledge and facilitate the acquisition and storage of memories for new related concepts presented within the reconsolidation window. Thirty-seven undergraduate students attended an expository-dialogue theoretical lecture and 48 hours later were assigned to each of two groups: GL (Reading Group) who read a short text and GT (Test Group) who performed a test composed by multiple-choice and fill-in-the-blank questions. Both educational materials were related to lecture content. Then, all participants attended a second class in which a new content was presented. Forty-eight hours later, a memory test (TM) about the new concepts was conducted. Overall, our results detected no difference between GL and GT. However, several of the analyzes conducted revealed an effect of the individuality regarding performance on the TMs. In other words, students with high percentage of correct answers maintained their good performance regardless of the method used to induce retrieval. Despite our study having several limitations, it is imperative that we continue to study memory updating processes in the educational context. It will only be possible to adapt the Brazilian educational system to support learning with evidence, especially those drawn from the complexity of a classroom.